2019
DOI: 10.1080/10508422.2019.1705159
|View full text |Cite
|
Sign up to set email alerts
|

Empathy as a predictor of prosocial behavior and the perceived seriousness of delinquent acts: a cross-cultural comparison of Argentina and Spain

Abstract: Empathy is very relevant to sociomoral development, especially in relation to prosociality and the penalization of acts as faults and crimes (sociomoral judgment).The objective of this research paper was to test whether empathy is a predictor of prosociality and the penalty of acts among young people in Argentina and Spain. The Argentinian sample comprised 215 high school and university students (67 males; average age 18.57, SD = 0.81). The Spanish sample comprised 199 university students (50 males; average ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 33 publications
1
15
0
5
Order By: Relevance
“…As background, EI in adolescents has been associated with better interpersonal relationships, higher levels of subjective well-being, better school performance, and mental health (MacCann et al, 2020;Nyarko et al, 2020). Meanwhile, empathy has been related to better interpersonal skills and greater prosocial behavior (Rodriguez et al, 2021;.…”
Section: Article In Pressmentioning
confidence: 99%
“…As background, EI in adolescents has been associated with better interpersonal relationships, higher levels of subjective well-being, better school performance, and mental health (MacCann et al, 2020;Nyarko et al, 2020). Meanwhile, empathy has been related to better interpersonal skills and greater prosocial behavior (Rodriguez et al, 2021;.…”
Section: Article In Pressmentioning
confidence: 99%
“…as conductas prosociales son aquellas que buscan ayudar a otra persona o al resto de la sociedad, son beneficiosas para estas y evitan conductas antisociales y actitudes agresivas (Martí-Vilar, Corell-García & Merino-Soto, 2019;Rodriguez, Martí-Vilar, Esparza Reig & Mesurado, 2019). Estas conductas se consideran un aspecto básico en cualquier sociedad (Moñivas, 1996).…”
unclassified
“…Los valores sociales están directamente relacionados con sus manifestaciones en forma de conductas (Cornelissen, Dewitte & Warlop, 2011). Los valores y habilidades sociales de cooperación se manifiestan con conductas prosociales hacia los demás (Rodriguez et al, 2019), mientras que los valores más individualistas se relacionan con comportamientos menos prosociales (Innamorati et al, 2018).…”
unclassified
“…Low cognitive empathy, in particular, is found to be related to offending (Bock & Hosser, 2014;Jolliffe & Farrington, 2004;van Langen et al, 2014) and low general empathy is found to predict juvenile recidivism (Narvey et al, 2021). A greater severity of empathy deficiency is associated with a higher propensity to engage in interpersonal violence (Mariano et al, 2016;Trivedi-Bateman, 2015), a higher frequency of offending (Jolliffe & Farrington, 2007, and less severe perceptions of the seriousness of criminal acts (Marcelo Rodriguez et al, 2021). Notably, empathy deficits are most commonly observed with interpersonal rule-breaking, such as person-toperson violence involving direct contact with the victim (Jolliffe & Farrington, 2007) over more impersonal offences such as property crime (Bach et al, 2017;Mariano et al, 2016).…”
Section: The Relationship Between Weak Empathy and Antisocial And Criminal Behaviourmentioning
confidence: 99%